PERFORMANCE MANAGEMENT OF ZAKAH USING INDEX ZAKAH NATIONAL IN THE BAZNAS PROVINCE OF NORTH SUMATRA - Sri Rahayu; Asmuni Asmuni; Marliyah Marliyah (Proceeding International Seminar of Islamic Studies, 2021)
This research aims to measure the performance of zakat management based on the ratio of the National Zakat Index (IZN) at Baznas in North Sumatra Province. The research method used is a qualitative study with a descriptive analysis method. This study provides an overview of the performance of zakat management from the macro dimension (the role of government and society) and the micro dimension (the institutional zakat and the impact of zakat on mustahik). Based on the calculation results of Baznas IZN calculation in the macro dimension, it is worth 0.78, meaning that this index is in the good category and in the micro dimension is 0.74 this index is in the good category. The aggregate result of the National Baznas IZN value is 0.76, which illustrates the achievement of zakat management in the good category. Keyword: Performance, Zakah, Baznas, National Zakat Index (IZN)